The Influence of Understanding the History of Islamic Culture and Moral Beliefs on the Morals of High School Students - Alam, M. Syahrul Qhodi; Rahman, M. Faqih Syifa; Hidayah, Nurul; Dewanti, Sintha Sih (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2025)
Understanding of the subjects of Islamic religious education, especially the history of Islamic culture (HIC) and moral belief, plays an important role in the formation of students' morals in the school environment. This study aims to analyze the influence of students' understanding of the subjects of HIC and moral beliefs on their morals in SMA Muhammadiyah 5 Yogyakarta. The approach used is quantitative with correlational methods to test the relationship between variables using multiple linear regression analysis. The Data were obtained through the distribution of questionnaires and tests to Class XI students as research subjects, focusing on the level of understanding of the two subjects and their implications for everyday morals. The results of the analysis showed a positive and significant influence between the understanding of HIC and moral beliefs on student behavior, either partially or simultaneously, this is evidenced by the value of F count of 44.038, which is greater than F table (4.01). The higher the level of students' understanding of HIC materials and moral beliefs, the better the morals reflected in their lives, both in the school environment and outside the school. This finding shows the importance of strengthening HIC learning and moral belief in an integrated manner in improving the moral quality and character of students in Islamic-based secondary schools.